The Use Of Visum Et Repertum As A Medical Legal Aspect To Foreign Tourists As Victims Of Sexual Violence In Indonesia - Dewi, Ni Luh Putu Ratih Sukma; Widiatedja, I Gusti Ngurah Parikesit (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2025)
This research discusses the Visum et Repartum policy as one of the use of medicolegal aspects to foreign tourists as victims of sexual violence in Indonesia. In several cases, victims are often embarrassed, insecure and even hesitant to report the perpetrator to the authorities due to the lack of evidence to support the victim of sexual violence. One solution that can be taken for victims of sexual violence is by carrying out Visum et Repartum. The problem arises regarding the settlement through the post-mortem, there has been a vacuum in the norms governing the guidelines for implementing the post-mortem. The results show that various regulations in the existing law do not regulate in detail and firmly the guidelines for implementing Visum et Repartum for victims of sexual assault in Indonesia, in order to support those who have been harmed by it often have difficulty reporting it to the authorities and proving it in KUHAP. In this research, the Visum et Repartum arrangements for foreign tourists who are victims of sexual violence in Indonesia are regulated by several laws and regulations in Indonesia, one of which is regulated by the Tourism Law and the Sexual Violence Crime Law. The form of legal regulation regarding the appropriate implementation of Visum et Repartum for foreign tourists who will be covered by the new law as victims of sexual assault (Ius Constituendum) can be in the form of regulations or policies that specific regulate law enforcement guidelines for the implementation of Visum et Repertum in Indonesia. In practice, currently there are no regulations governing the implementation of Visum et Repartum for foreign tourist victims properly and correctly in accordance with Indonesian regulations.